Impact of micronutrients foliar spray on value addition in wheat - Mohan, Devinder; Gill, Subhash Chander; Gupta, Raj Kumar (Journal of Cereal Research, 2016)
Improvement in yield and quality is paramount in wheat breeding. Besides genetic attributes, some nongenetic factors have also been successfully tried to enhance wheat yield. In this endeavor, application of micronutrients like iron, zinc, manganese, copper has been widely reported in wheat (Ali et al., 2009; Khan et al., 2010; Zain et al., 2015). Enhanced density of these micro-nutrients in wheat grain has been advocated to address hidden hunger (Cakmack et al., 2004; Welch and Graham, 2004). Bio-fortification efforts in India have provided couple of genotypes with enhanced zinc content in the wheat grains. Besides grain yield, enhanced micronutrient content in the soil or in the grains, has also resulted in higher protein content (Mohan et al. 2009; Zeidan et al., 2010). Micronutrients are involved in numerous physiological processes that are essential for plants. Copper plays an important role in the metabolism of N compounds. Manganese, along with Zn, has an effect on protein biosynthesis by adjusting the activity of peptidases and controlling protein metabolism (Hänsch and Mendel, 2009). Although micronutrients grain density in different zones, impact on grain quality, location effect and the approach to harness these grain qualities had been addressed in the Indian wheats (Mohan et al., 2009 & 2013; Mohan and Gupta, 2008), there is no study on the impact of their foliar application in grain quality characteristics. The present investigation is an exploratory study to gauge the impact of sprayed micronutrients on some grain quality parameters.